Prolonged emergency and derogation of human rights: Why the European Court should raise its immunity system - Triestino Mariniello (German Law Journal, 2019)
States of emergency pose the most significant challenges to the safeguarding of fundamental rights and civil liberties. Crises are generally characterized by a strengthening of the executive to the detriment of judicial authority and parliamentary oversight. One of the immediate consequences of emergencies is the absence of effective domestic mechanisms of supervision of the executive. The gradual replacement of the judicial role with police operations represents a symptom of how prolonged emergencies prompt the eclipse of legal certainty and lead to the rapid and irreversible degradation of public institutions.